Evaluating pedagogical competence of pre-service teachers in Islamic education: Insights from School Field Practice program - Wahdah, Wahdah; Elfri, Rini (Journal of Educational Management and Instruction (JEMIN), 2024)
Teacher competence is a key determinant of educational quality, particularly in the field of Islamic education where both pedagogical skills and religious teachings must be integrated. This study aims to evaluate the pedagogical competence of pre-service teachers from the Islamic Education Program at Universitas Muhammadiyah Pontianak during their School Field Practice (PLP). Using a mixed-methods approach, the research assesses pre-service teachers' abilities in designing, implementing, and evaluating lesson plans. Quantitative data were collected through questionnaires, while qualitative data were derived from lesson plans and reflective documentation. The findings reveal that pre-service teachers demonstrated strong competence in lesson planning and implementation, with average scores placing them in the "Good" to "Very Good" categories. However, their ability to evaluate their teaching performance showed room for improvement, suggesting the need for more structured training in reflective practice. The study concludes that while the PLP program effectively prepares pre-service teachers in lesson planning and delivery, further emphasis on self-assessment and evaluation is essential for continuous professional development. These findings provide valuable insights for improving teacher training programs in Islamic education and highlight the importance of integrating reflective practices into the curriculum.